Dynamics of political violence : a process-oriented perspective on radicalization and the escalation of political conflict - Bosi, Lorenzo; Demetriou, Chares; Malthaner, Stefan (Mobilization series on social movements, protest, and culture., 2014)
Dynamics of Political Violence examines how violence emerges and develops from episodes of contentious politics. By considering a wide range of empirical cases, such as anarchist movements, ethno-nationalist and left-wing militancy in Europe, contemporary Islamist violence, and insurgencies in South Africa and Latin America, this volume of research identifies the forces that shape radicalization and violent escalation and contributes to the process-and-mechanism-based models of contentious politics that have been developing over the past decade in both sociology and political science.